TERM-TERM PENTING TERKAIT HADITS DALAM KAJIAN HUKUM ISLAM - Hani Sholihah (An-Nahdliyyah: Jurnal Studi Keislaman, 2023)
This article discusses important terms related to hadith, such as several terms that are synonymous with hadith, namely sunnah, khabar, and athar. Although not significant, there are differences between these four terms. In addition, there are other terms related to hadith, namely qauli hadith, fi`li hadith, and taqriri hadith; sanad, matan, rawi, and mukharrij. This article aims to provide an understanding of the meaning and use of these terms in Islamic law. Through analysis and review of various references as data sources in literature research, this article aims to provide a better understanding of the differences and similarities between hadith, sunnah, khabar, and athar; qauli hadith, fi`li hadith, and taqriri hadith; sanad, matan, rawi, and mukharrij. This will assist scholars and practitioners of Islamic law in interpreting and applying Islamic law more accurately and comprehensively. With a better understanding of this terminology, it is hoped that this article can contribute to the development of Islamic law studies and increase Muslim understanding of the sources of Islamic law itself.